Perencanaan Penjadwalan Preventive Maintenance Mesin Jet Dyeing Menggunakan Pendekatan Critical Path Method di PT XXX - Alifah Nur Astari; Tiaradia Ihsan; Teten Hidayat (Universitas Widyatama, 2023)
Jet Dyeing Machine is a machine used in the textile industry to dye fabric materials with efficiency and large-scale production capacity. PT XXX faces a high frequency of damage and total lost time on several components of production machines, so proper maintenance and maintenance in accordance with standards needs to be carried out to reduce the frequency of damage and total lost time and extend the service life of components. The CPM approach can help in creating an effective maintenance and maintenance schedule so that production can run smoothly and efficiently. This study aims to plan maintenance schedules and preventive maintenance on production machines at PT XXX using the CPM approach. The results of the analysis show that routine maintenance and maintenance of machine components is very important to reduce the frequency of damage and total lost time that can have an impact on production losses. The maintenance schedule must be considered carefully so as not to interfere with production and not to interfere with the performance of the machine and maintenance personnel must have adequate knowledge and skills to carry out maintenance and maintenance properly in accordance with the established SOP. Total losses due to wasted lost time can be reduced by 24% from the original. Repair and replacement of components that often experience damage need to be done to reduce the frequency of damage and total lost time on PT XXX production machines